Confirmatory factor analysis of the Multidimensional Inventory of Perfectionism in Sport. (September 2016) - Madigan, Daniel J.
Abstract: Objectives and method: The Multidimensional Inventory of Perfectionism in Sport (MIPS; Stoeber, Otto, & Stoll, 2006) is a commonly used measure of perfectionism in sport. However, there is limited empirical evidence supporting its subscale structure and composition. Therefore, the present study investigated the factor structure of the MIPS in a sample of 470 athletes (mean age 20.0 years). Results: Confirmatory factor analysis showed that the data supported the hypothesized four-factor structure of the MIPS, differentiating: striving for perfection, negative reactions to imperfection, parental pressure to be perfect, and coach pressure to be perfect. Conclusions: The findings suggest that the MIPS has acceptable factorial validity and therefore may be a useful measure to explore individual differences in perfectionism in sport. Highlights: CFA of the Multidimensional Inventory of Perfectionism in Sport (MIPS). Data from 470 athletes were analyzed. The hypothesized four-factor structure provided an adequate fit to the data. The findings suggest the MIPS has acceptable factorial validity. Therefore, the MIPS may be a useful measure of perfectionism in sport.